The Performance of Several Current Interpolation Methods for Variability of cations in Groundwater in Esfarayen Plain, Iran: A Case Study - Ali Mahmoodnia; Morteza Mousavi; Farshad Golbabaei Kootenaei; Mahdi Asadi-Ghalhari (Hamadan University of Medical Sciences, 2022)
Acquiring information about groundwater quality is essential in developing management strategies. In this article, spatio-temporal variations of cations in groundwater in Esfarayen plain were investigated using data monitored in 134 groundwater wells, active in 1988, and 47 wells, active in 2019. To evaluate groundwater quality, interpolation methods have been used to interpolate existing limited spatial data. The performance of 8 current interpolation methods on the data for the two selected years (1988 and 2019) was compared. Finding the optimum interpolation method for the considered groundwater quality parameters is essential. Cross-validation and three indexes of R2, mean absolute error (MAE), and root mean square error (RMSE) were used to compare the performance of the methods. By identifying universal kriging (UK) and global polynomial interpolation (GPI) methods as the optimum methods and using those for the selected years (1988 and 2019), spatial variation of the concentration of cations in groundwater across the plain has been presented. In 1988, the maximum concentration of the cations occurred in the southwest of the plain (about 80 mg/L), and the minimum concentration of the cations was observed in the northwest of the plain (approximately 8 mg/L). Similarly, in 2019, the highest concentration of the cations was found in the southwest of the plain (almost 64 mg/L), and its lowest concentration was observed in the northeast of the plain (roughly 13 mg/L). Moreover, temporal variations of the concentration of cations in groundwater from 1988 to 2019 have also been presented. The concentration of the cations increased by approximately 23 mg/L in the northwest and decreased to about 37 mg/L in the southwest of the study area from 1988 through 2019. According to the results, changes in the quality of groundwater are a complex problem and it is necessary to adopt proper strategies to reduce its adverse effects.